2022
DOI: 10.3748/wjg.v28.i31.4249
|View full text |Cite
|
Sign up to set email alerts
|

Insights into induction of the immune response by the hepatitis B vaccine

Abstract: After more than four decades of hepatitis B virus (HBV) vaccine implementation, its safety and efficacy in preventing HBV infection have been proven and several milestones have been achieved. Most countries have included HBV immunization schedules in their health policies and progress has been made regarding universalization of the first HBV vaccine dose at birth. All of these actions have significantly contributed to reducing both the incidence of HBV infection and its related complications. However, there ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 118 publications
2
10
0
1
Order By: Relevance
“…This result aligns with the protection level expected for second-generation vaccines. Indeed, it is estimated that for these vaccines, around 5 to 10% of the vaccinated population do not induce protective immunity [27]. Similar response rates have been reported in previous studies evaluating the efficacy of GeneVac in healthy infants, adolescents, and adults in India [21][22][23][24][25][26].…”
Section: Discussionsupporting
confidence: 60%
“…This result aligns with the protection level expected for second-generation vaccines. Indeed, it is estimated that for these vaccines, around 5 to 10% of the vaccinated population do not induce protective immunity [27]. Similar response rates have been reported in previous studies evaluating the efficacy of GeneVac in healthy infants, adolescents, and adults in India [21][22][23][24][25][26].…”
Section: Discussionsupporting
confidence: 60%
“…Although there is no comparative study among children, our finding is consistent with results observed among adults in Africa [ 92 ]. The lack of protective immune response among people living with HIV has been linked with reduced CD4 cell count and B-cell dysfunction [ 35 , 38 ] and factors such as viral load, sex, and age also influence immune response to HBV vaccine among people living with HIV [ 92 , 93 ]. Our finding further supports routine PVST for children living with HIV after completion of the primary series.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors including perinatal host, nutritional, environmental, and immunization-related factors such as suboptimal dosing, site of administration, and reduced potency due to poor vaccine storage and handling conditions, could have accounted for the nonresponse among the under 5 children in the studies [ 31 , 94 ]. While the cellular mechanisms involved in nonresponse to HBV vaccination remain unclear, impaired lymphocyte activation has been implicated [ 38 , 95 ]. Interventions to address nonresponse among children will depend on largely the prevailing health status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that hepatitis B is contribute to onset or exacerbation of autoimmune disorders via molecular mimicry [ 40 , 41 ]. Whereas, it has been proven the safety and efficacy in preventing HBV infection [ 42 , 43 ], and ruled out any confirmed evidence that HBV vaccine causes autoimmune disorders [ 44 ]. HBV vaccine contains yeast, aluminium, thimerosal, hepatitis B surface antigen epitopes, and adjuvants, which may result in hepatitis B vaccine being associated with autoimmune diseases among susceptible adult vaccine recipients [ 44 ].…”
Section: Discussionmentioning
confidence: 99%